(untitled) (KULT_online, 2013)
In the conference proceedings Pop, Populäres und Theorien. Forschungsansätze und Perspektiven zu einem prekären Verhältnis in der Medienkulturgesellschaft (Pop, the Popular, and Theories. Research Methods and Perspectives on a Precarious Relationship in the Media-Culture Society), the breadth of various theoretical approaches to the popular is made visible. The book emphasizes the importance of interdisciplinary discussion and analysis, in which methods from cultural, communication and media studies are connected. In spite of a number of shortcomings with regard to the book’s overall structure and argumentative line, it can be regarded as a wide-ranging and meritorious presentation of current theoretical discussions in the German-speaking popular culture debate.